Implementation of Video Modeling Animation on Toilet Training Ability in Autism Spectrum Disorders - Andriyani, Septian; Putri, Suci Tuty (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: Toilet training is critical for the quality of life of individuals with autism spectrum disorders (ASD) and other developmental disabilities. This is essential because an individual with ASD is often late to acquire these skills or fails to do so. This study aims to identify and analyze the implementation of animation video modeling (AVM) to improve toilet training abilities in children with autism spectrum disorders. MATERIALS AND METHODS: The research uses a quantitative descriptive approach with an experimental research design using One Group Pretest Posttest Design. The pretest was carried out before the intervention, and the posttest was carried out after the AVM gave toilet training intervention. The sampling technique was in the form of total sampling, namely 50 children(43 boys and 7 girls) with autism. The research instrument was a checklist of statements. Data analysis using the Wilcoxon Sign Rank Test. RESULTS: The results showed that almost half of the ability levels of children with autism before being given AVM toilet training were in a suitable category, nearly half of the children with autism after being given treatment were in a good type with a p-value 0.011; there was a significant difference in the level of ability before and after given an AVM. CONCLUSION: AVM is one of the effective interventions to improve toilet training abilities in children with ASD. AVM can help children in the elimination process that can be done independently in improving the quality of life in children with autism.